Calcium Channels: Noteworthy Regulators and Therapeutic Targets in Dermatological Diseases - Wang, Min; Sun, Yaoxiang; Li, Linli; Wu, Peipei; DKW, Ocansey; Shi, Hui (Frontiers in Pharmacology, 2021)
Dysfunctional skin barrier and impaired skin homeostasis may lead to or aggravate a series of dermatologic diseases. A large variety of biological events and bioactive molecules are involved in the process of skin wound healing and functional recovery. Calcium ions (Ca2+) released from intracellular stores as well as influx through plasma membrane are essential to skin function. Growing evidence suggests that calcium influx is mainly regulated by calcium-sensing receptors and channels, including voltage-gated, transient potential receptor, store-operated, and receptor-operated calcium channels, which not only maintain cellular Ca2+ homeostasis, but also participate in cell proliferation and skin cell homeostasis through Ca2+-sensitive proteins such as calmodulin (CaM). Furthermore, distinct types of Ca2+ channels not merely work separately, they may work concertedly to regulate cell function. In this review, we discussed different calcium-sensing receptors and channels, including voltage-gated, transient receptor potential, store-operated, and receptor-operated calcium channels, particularly focusing on their regulatory functions and inherent interactions as well as calcium channels-related reagents and drugs, which is expected to bridge basic research and clinical applications in dermatologic diseases.